Martial law in the Philippines : lessons and legacies, 1972-2022 - De Jesus, Edilberto C.; Baysic, Ivyrose S. (Quezon City, Philippines : Bughaw, 2023)
The writers in this book lived through martial law and tell it like it was$1 (Ba fake and tarnished gold. Dictatorship and its aftereffects explode on the scene as twenty-two experts take us through the ups and downs of seven presidential administrations since that fateful 1972 declaration. Each specialist focuses on a particular topic. The resulting collection offers something for everyone. Under Society and Culture, readers can select from cultural politics, dictatorial fantasies, populism and authoritarianism, religion, urban poor organizing, indigenous people, Filipino-Chinese identity, and Filipino values in a global context. More interested in Political Economy and Governance? Explore party politics, electoral reform, media roles, the Constitution, population management, and crony economic governance. s
Part 1. Society and Culture -- Part 2. Political Economy and Governance -- Part 3. Peace and Security.
Includes index.
Keywords: MARTIAL LAW -- PHILIPPINES; PHILIPPINES -- POLITICS AND GOVERNMENT -- 1973-1986